Pregnancy intentions and its associated factors among married women in resunga, Gulmi, Nepal - Rita Karki; Surendra Maharjan; Ganesh Khatiwada; Junu Shrestha (Wolters Kluwer Medknow Publications, 2023)
Pregnancy intention refers to a women's thinking at the time she became aware that she was pregnant. It can be categorized as intended and unintended. Identifying pregnancy intentions during prenatal periods help to employ careful monitoring of pregnancy that is at high risk for mother and children's health outcomes. Unintended pregnancy is a contributing factor for maternal and infant mortality, which is still high in Nepal. Reproductive and family planning program should incorporate pregnancy intention domains in health education and counseling with priority to design program to address and reduce unintended pregnancy. This brief research examines the pregnancy intentions and its associated factors among married women so that it could identify the intentions of pregnancy and factors influencing unintended pregnancy and could be useful to improve and maintain the health and well-being of women, family, community, and nation.